Engagement Analysis and Influencer Fees A Study on Reconnecting Brands with Their Customers - Iskandar, Eky (Journal of Social Commerce, 2023)
This observe investigates the relationship among influencer engagement metrics and costs in reconnecting manufacturers with former customers. Utilizing a quantitative approach, the studies analyzes how exclusive varieties of engagement along with likes, feedback, and shares have an effect on marketing campaign overall performance and the way various influencer fees impact typical fulfillment. Findings reveal that better engagement levels, mainly via feedback and stocks, extensively beautify conversion rates and customer recapture. Additionally, multiplied influencer charges are definitely correlated with better marketing campaign outcomes, emphasizing the importance of funding in influencer partnerships. The observe additionally highlights the various effectiveness of various influencer sorts, including celebrities, macro-influencers, and micro-influencers, supplying insights for brands to optimize their marketing techniques based totally on their goals and price range. These outcomes make a contribution to a extra nuanced knowledge of influencer marketing and offer actionable guidelines for enhancing campaign effectiveness.